Mind the Gap: Understanding Differences Between Sexual and Reproductive Health-Related Legal Frameworks on Paper and in Practice - Ferguson, Laura; Jardell, William; Lambert-Peck, Miles; Guo, Lillie; Lopez, Sophia; Canaves, Violeta; Filmer-Wilson, Emilie (Frontiers in Global Women's Health, 2022)
UNFPA recently developed a composite indicator to assess sexual and reproductive health (SRH)-related laws as part of the Sustainable Development Goals monitoring framework (Indicator 5.6.2). However, there is still little understanding of how best to ensure a supportive SRH-related legal framework can improve SRH outcomes. This research draws on country case studies (Colombia, Malawi, Uruguay, Zambia) to provide more generalizable lessons on the processes by which these laws are translated into practice and their impact on lived realities. Peer-reviewed and grey literature on laws and policies related to maternity care, contraception, sexuality education, HIV and HPV was reviewed. Key informant interviews were carried out with 8-16 people in each country, including representatives of government, civil society and academia to understand factors affecting implementation of relevant laws and policies. Findings were thematically analyzed by country and contextualized within each country’s score on Indicator 5.6.2 and relevant SRH outcome data. Across these countries, some common organizational steps help move from laws on paper to impacting people’s lives including budget allocation, development of technical guidance, health worker training, population awareness creation and demand generation. It is also important to address sociocultural challenges such as entrenched inequalities, conservative cultural and religious beliefs and the potential existence of customary law. Challenges can be encountered across all these steps and can vary based on the area of SRH: implementation of laws to reduce maternal mortality is generally less controversial than laws around abortion, often making the latter harder to implement. Local specificities in structures, systems and cultures bring opportunities and challenges, highlighting the need for tailored actions. A legal framework supportive to SRH is critical, particularly in the face of backlash against sexual and reproductive rights, but alone it is insufficient. Understanding that a generic pathway exists for moving laws into practice is a critical starting point for exploring the specificities of each national context as a way of identifying entry points for action. These findings can be used to inform advocacy and monitoring to help ensure that the potential benefits of supportive SRH-related laws can be realized in these four countries and around the world.